Changes in primitive reflexes in older adults and their relationship to mental health indices: An experimental investigation - Erzsébet Stephens-Sarlós; Eliza Toth; Ferenc Ihász; Zoltán Alföldi; Angéla Somogyi; Attila Szabo (Experimental Gerontology)
The reemergence of primitive reflexes (PRs) in older age is related to cognitive impairment. Currently, there are no means to prevent or slow their reappearance, but research evidence exists for their control in children. Therefore, this experiment investigated whether a 16-week special sensorimotor exercise program could benefit older adults and whether the intervention-induced changes (if any) may be associated with various indices of mental health. Of 115 adults over 60, 95 completed the study (mean age = 76.37 ± SD = 7.04 years, 22 % men). The experimental group (n = 38) showed an almost threefold decline in PRs compared to controls. In contrast, the control group (n = 57) exhibited a nearly threefold increase in PRs compared to the intervention group. Cognitive function increased in the experimental but not in the control group. Changes in PRs over the 16-week intervention were positively related to negative mental health indices (hopelessness and perceived stress) and negatively related to well-being. These findings suggest that the here-presented mild sensorimotor exercises could affect older adults' reemerging PRs and that changes in PRs are associated with mental health benefits. These results may open new research avenues toward preventing cognitive and psychological decline in older adults.